Design and development of e-module based on Problem Based Instruction (PBI) on Object-Oriented Programming Course in University - Yuliawati Yunus; Firna Yenila (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2018)
Ths study aim to design and develop e-module based on PBI in this product will be tested feasibility with test validity, practicality and efecticity. This research used for this research and development with 4d development satge design, where the population of this study is informatics Engineering Education Study Program of west sumatera. Results of the five validator in test validation of e-module based on PBI 90.4% can be interpreted Very Valid Used. Overall assessment of the practicality of e-Module based on PBI-based as a learning resource of 83.3% can be interpreted Practically Used. And the effectiveness of the interactive module as a learning resource of 80.92% can be interpreted Effectivelyused.Problems in this study low for using electronic learning media of Pemograman Berbasis Objek II (PBO II) Course in study program of informatic engineering education. E-module based on problem based instruction (PBI) has not been used. That’s because lecturers are accustomed to give practicum module in the form of power point or printed handout in seperate material in every indicator in lecture process in labor or class.